Disabling disease codes predict worse outcomes for acute medical admissions - Sanjay H. Chotirmall; Sarah Picardo; Judith Lyons; Michael K. Dalton; Deirdre O’Riordan; Bernard Silke (2014)
Concurrent with an extension in longevity, a prodrome of ill-health ('disability' identifiable by certain International Classification of Disease (ICD) 9/ICD10 codes) predates the acute emergency presentation. To date, no study has assessed the effect of such 'disability' on outcomes of emergency medical admissions.To devise a new method of scoring the burden of 'disability' and assess its relevance to outcomes of acute hospital admissions.All emergency admissions (67 971 episodes in n = 37 828 patients) to St James' Hospital, Dublin, Ireland over an 11-year period (2002-2012) were studied, and 30-day in-hospital mortality and length of stay were assessed as objective end-points. Patients were classified according to a validated 'disability' classification method and scored from 0 to 4+ (5 classes), dependent on number of ICD9/ICD10 'hits' in hospital episode codes.A disabling score of zero was present in 10.6% of patients. Scores of 1, 2, 3 and 4+ (classified by the number of organ systems involved) occurred with frequencies of 23.3%, 28.7%, 21.9% and 15.5% respectively. The 'disability' score was strongly driven by age. The 30-day mortality rates were 0.9% (no score), 2.6%, 4.1%, 6.3% and 10.9%. Surviving patients remained in hospital for medians of 1.8 (no score), 3.9, 6.1, 8.1 and 9.7 days respectively. High 'disability' and illness severity predicted a particularly bad outcome.Disability burden, irrespective of organ system at emergency medical admission, independently predicts worse outcomes and a longer in-hospital stay.